Basic research Structure-activity relationships of taxoids: a molecular descriptors family approach - Bolboacă, Sorana; Jäntschi, Lorentz (Archives of Medical Science, 2008)
Introduction: Taxoids, groups of diterpenoid cyclodecanes isolated from the genus Taxus, are known and used as anticancer agents. Starting from the successful results obtained by an original molecular descriptors family on structure-activity relationships (Jäntschi and Bolboacă, 2007), the aim of the research was to investigate and to assess the estimation and prediction abilities of this approach on a sample of taxoids. Material and methods: The molecular descriptors family on structure-activity relationships approach was used in order to characterize the link between structure of a sample of thirty-four taxoids and associated growth inhibition activity. The chance correlation of obtained models was investigated using random assignment of compounds in leave-one-out analysis and training versus test experiments. Results: One model with one descriptor and two multivariate models, one with three and the other with five descriptors, proved to have estimation and prediction abilities. Statistical characteristics of the models revealed that the MDF-SAR model with five descriptors has excellent estimation and prediction abilities compared with models with one or three descriptors. Conclusions: The molecular descriptors family on structure-activity relationships approach proved its usefulness in characterization of growth inhibition activity of studied taxoids. Further studies on new taxoids are necessary in order to assess the robustness and prediction ability of the MDF-SAR model with five descriptors.